The role of intrinsic and extrinsic rewards in committing violence during combat: A cross‐sectional study with former combatants in the DR Congo. Issue 3 (17th October 2016) - Haer, Roos; Hermenau, Katharin; Elbert, Thomas; Moran, James K.; Hecker, Tobias
Abstract : It has been postulated that the violent behavior that characterizes armed conflict is reinforced by the possibility of receiving rewards. The present study examined the potential influence of two types of rewards in an ongoing setting of conflict: extrinsic and intrinsic rewards. Former combatants active in the Democratic Republic of the Congo ( N = 198) were interviewed and questioned about the way they were recruited, the offenses they committed during combat, their level of perceived intrinsic rewards (i.e., appetitive perception of violence), and the number of received extrinsic rewards during their time in the armed group (e.g., money, extra food, alcohol, or drugs). A moderated multiple regression analysis showed that the number of received extrinsic rewards and the level of intrinsic rewards were significantly positively related to the number of different types of offenses committed. In contrast to our expectations and previous findings, the recruitment type (forced conscription vs. voluntary enlistment) did not moderate this relation. Our findings suggest that both types of rewards play a role in committing violence during combat. We suggest, therefore, that reintegration programs should not only consider the influence of extrinsic rewards, but also need to address the influence of intrinsic rewards to counter violent behavior among former combatants. Aggr. Behav. 43:241–250, 2017. © 2016 Wiley Periodicals, Inc.